Study of Earthquake Preparedness in Kathmandu City, Nepal - K.C., Rodit (Journal of APF Command and Staff College, 2022)
Earthquakes cannot be predicted but effective planning and preparation may reduce the impact. Impacts from earthquake risk is believed to be increasing very rapidly mainly due to the improper development activities. People require to have basic knowledge on preparing themselves to mitigate the impacts from the earthquake. This paper studied the effectiveness of implementation of knowledge and skills to mitigate the impact of earthquake by focusing on the knowledge and ability of the household members in the community. This study also helped the respondents and institutions and stakeholders who were the part of this research to reflect, analyse and assess their own earthquake preparedness measure. It is seen that there is a necessity for a sound coordination and realization on importance of better preparedness which is essential to mitigate the impact from the earthquake.